Handbook of research on transitional justice and peace building in turbulent regions - Cante, Freddy; Quehl, Hartmut (Advances in public policy and administration (APPA) book series, 2016)
"This book focuses on current issues facing nations and regions where poverty and conflict are endangering the lives of citizens as well as the socio-economic viability of those regions, highlighting crucial topics and offering potential solutions to problems relating to domestic and international conflict, societal safety and security, as well as political instability"--